KAJIAN POTENSI PEMBANGKIT LISTRIK TENAGA MIKRO HYDRO (APLIKASI DESA RANTAU SULI - KEC. JANGKAT - KAB. MERANGIN â JAMBI) - Dahlan, Musdar Bin; Purba, Ladiman (Techno Jurnal Ilmu Teknik, 2010)
Â The Micro Energy Alternator Hydro is processing water potential energy conversion to become a real electric energy is of benefit to public life, especially public in district - purilieus that is is not flown by electric current PLN. Planning study of this Hydro Micro Energy Alternator in strarting from study literature is relating to making of Micro Energy Alternator Hydro. Then does survey to location that is in hamlet Rantau Suli, to be able to determine regulus cross-area, gauging of water debit and water shoot altimetry. Then data processing covering calculation energy? power, calculation to determine type or specification of equipments mechanical, spesifkasi equipments electrical, installation of civil. At planning of this Hydro Micro Energy Alternator applies water debit 0,99 m3/s, water head used is 18,96 m, applies turbine type crossflow T14 and electricity which can be yielded 137,823 kVA. Generator applied is synchronous generator 4 kutup, with frequency 50 Hertzs. Civil design applies bagwark stone dam type by strenghtened [by] concrete. Resident housing which can be flown electricity 280 housing units with every housing unit gets electricity 480 VA.Â Keyword: height, debit, turbine crossflow, micro hydro, electrical energy.